Analysis of Occupational Safety and Health Risks in Scaffolding Work Using HIRADC and JSA Methods at PT. XYZ - Maulana, Muhammad Fajar; Priyana, Eftha Dhartikasari; Purwanto (Journal of Advances in Information and Industrial Technology, 2026)
This study aims to analyze occupational safety and health (K3) risks in scaffolding work at PT. XYZ is using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) and Job Safety Analysis (JSA) methods. The study used a quantitative descriptive approach with field observation methods, structured interviews, and documentation of 11 respondents during the period August to December 2025. The results of the hazard identification showed that there were 17 potential hazards classified into 13 risk items. Risk assessment using a risk matrix of 5×5 showed that there were 2 high risks (R=15) and 11 moderate risks. The highest risk comes from work at height on the installation and painting of scaffolding. After the implementation of hierarchical-based controls, all high risks were successfully downgraded to medium risk, with an average reduction in risk values by 40%. The JSA analysis produced 37 safe work steps that can be used as the basis for the preparation of SOPs and safety briefings in the field. The results of the study show that the integration of HIRADC and JSA methods is able to increase the effectiveness of comprehensive risk identification and control in construction work.